A new solution for vibroacoustic analysis of two-dimensional cylindrical shells partially liquid-filled or partially submerged in fluid. (June 2020) - Guo, Wenjie; Feng, Qingsong; Li, Tianyun; Zhu, Xiang; Miao, Yuyue
Highlights: This study proposes a new method with a wide application scope and good accuracy. Antisymmetry modal frequencies are different from the symmetry ones. Far-field sound pressures comes up to be maximum just right below the shell. Abstract: In this study, a semi-analytical method is proposed to study the vibration and acoustic radiation of a two-dimensional cylindrical shell partially coupled with internal fluid. Different from the conventional vibroacoustic model of cylindrical shells, two different coordinates are established to describe the motion of the shell and the internal fluid respectively. One coordinate system is established on the free surface, where the sound pressure release boundary condition is satisfied automatically by constructing a sine series expression of sound pressure. Meanwhile, with the center of the shell's cross section as the origin, the other is established to describe the motion of the shell. Then the Galerkin method and the coordinate transformation technique are adopted to deal with the velocity continuous condition on the partially coupled interface. Finally, the vibroacoustic response can be solved theoretically. The applicability and reliability of the present method are validated by comparison with the finite element method via the free vibration, forced vibration and sound radiation cases. The present method is also extended to deal with the vibration and sound radiation of shell coupled with external fluid successfully. Generally speaking, this study proposes a new method to the solution of the vibroacoustic behaviours of an elastic cylindrical shell partially coupled with fluids theoretically, with a wide application scope and good accuracy.